Similar and Additive Effects of Ovariectomy and Diabetes on Insulin Resistance and Lipid Metabolism. (5th March 2015) - Tawfik, Shady H.; Mahmoud, Bothaina F.; Saad, Mohamed I.; Shehata, Mona; Kamel, Maher A.; Helmy, Madiha H.
Abstract : Type 2 diabetes mellitus (T2DM) is among the leading causes of death in postmenopausal women. The disruption of ovarian function may contribute to the incidence of T2DM. The purpose of this study was to investigate the effects of ovariectomy and T2DM on glucose and lipid homeostasis, perilipin levels in adipose tissues, as a lipolytic regulator, and levels of certain adipokines. Ovariectomized (OVX) rats were used as a model for postmenopausal women. The study was performed on sham, OVX, sham diabetic, and OVX diabetic female rats. The results indicated that ovariectomy alters adipose tissue metabolism through reducing perilipin content in white adipose tissue (WAT); however it has no effect on perilipin level in brown adipose tissue (BAT). OVX diabetic females suffer from serious metabolic disturbances, suggested by exacerbation of insulin resistance in terms of disrupted lipid profile, higher HOMA-IR, hyperinsulinemia, higher leptin, and lower adiponectin concentrations. These metabolic derangements may underlie the predisposition for cardiovascular disease in women after menopause. Therefore, for efficient treatment, the menopausal status of diabetic female should be addressed, and the order of events is of great importance because ovariectomy following development of diabetes has more serious complications compared to development of diabetes as result of menopause.